Altered Th17/Treg ratio as a possible mechanism in pathogenesis of idiopathic membranous nephropathy. (May 2021) - Motavalli, Roza; Etemadi, Jalal; Soltani-Zangbar, Mohammad Sadegh; Ardalan, Mohamad-Reza; Kahroba, Houman; Roshangar, Leila; Nouri, Mohammad; Aghebati-Maleki, Leili; Khiavi, Farhad Motavalli; Abediazar, Sima; Mehdizadeh, Amir; Hojjat-Farsangi, Mohammad; et al.
Abstract: Idiopathic membranous nephropathy (IMN) as a single organ autoimmune disease is a main cause of nephrotic syndrome in adults which is determined through autoantibodies to podocytes proteins. Th17/regulatory T (Treg) balance has emerged as a prominent factor in the regulation of autoimmunity. In this study, we evaluated the balance of Th17 and Treg cells, expression level of related master transcription factors, cytokines and microRNAs in mononuclear cells of peripheral blood of 30 patients with IMN and 30 healthy individuals before treatment. No significant variation was observed in Th17 cell frequency, retinoic acid receptor‐related orphan nuclear receptor γt (RORɣt), signal transducer and Activator of transcription 3(STAT3), IL-17, and IL-23, while IL-21, IL-4, and IL-10 had significant increase in mRNA expression and protein level of peripheral blood mononuclear cells in IMN cases. Reduction in the percentage of Treg cells was also accompanied with significantly decreased expression of Forkhead box P3(FOXP3) and Transforming growth factor beta (TGF-β) in IMN patients compared to the control group. Our study revealed that Th17 cells themselves might not be engaged in the pathogenesis of newly diagnosed patients with IMN; however, decreased T reg cells and increased ratio of Th17/Treg lymphocytes might display a role in the pathogenesis of IMN before treatment.